Effect of the scanner background noise on the resting brain networks detected by functional magnetic resonance imaging - Rondinoni, Carlo; dos Santos, Antônio Carlos; Salmon, Carlos Ernesto G. (Revista Brasileira de Física Médica, 2015)
Resting state studies by fMRI are carried out in order to identify the brain networks responsible for their basal functioning, which are known as resting state networks. Although considered to be in rest, subjects are unavoidably under a massive charge of environmental acoustic noise produced by the magnetic resonance imaging equipment. Our aim was to verify if the massive auditory information input could mask the “real” resting state networks. The functional volumes were acquired when seven naïve subjects (four women) had their eyes opened under default echo planar imaging (EPI) sequences or during soft-tone sequences (slew-rate reduction), as allowed by a Philips Achieva 3T magnetic resonance imaging scanner. The sound pressure level difference between the default and soft sequences reached 12 dB. Experimental sessions consisted of two runs of seven minutes each under different levels of noise. The sequence of conditions was counterbalanced between subjects. The functional volumes were pre-processed in BrainVoyager and submitted to self-organizing group Independent Component Analysis (sogICA). The influence of the higher noise level was evaluated by identifying the BOLD components and by comparing the functional volumes of the five representative resting state networks under each condition (random effects – Independent Component Analysis). The results show that a lower level of noise may uncover functionally wider components. A t-test showed that the high noise condition induced significantly higher BOLD signal in the posterior cingulate cortex only. However, lower noise levels induced higher BOLD activity in the bilateral parietal lobule, bilateral superior frontal gyrus, and insula. Yet, the motor resting state network seems to be wider under low noise, reaching auditory areas in the temporal cortices, and an oscillatory component on the thalamus was identified in the low noise condition. The results indicate that a compromise should be taken into account when studying rest, balancing between noise reduction, and speed of acquisition.